Improving student's engagement - changing classroom discourse using teacher restorative professional development. (2016) - Rofe, Craig; Stewart, Mark; Wood, Matt
This paper introduces the concept of restorative teaching practice and argues that application of a restorative approach in teacher professional development may have positive outcomes for teachers and students' engagement. The majority of teachers exhibited a facilitator type role where less instructional discourse was observed with more positive feed forward discourse also observed. The majority of students were found to be more engaged with the changes in class discourse even when the students reported that the apparent level of task difficulty had been increased. The professional development's two staged approach ensured that the school was left with a sustainable process that could be utilised using internal staff.